2005
DOI: 10.1300/j019v27n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Self-Directed Behavioral Family Intervention: Do Therapists Matter?

Abstract: Behavioral family intervention is an effective form of intervention for the prevention and treatment of a wide range of emotional and behavioral problems in children. There is a growing need to address the accessibility of these services. This paper reviews the literature on self-directed interventions designed to help parents manage difficult child behaviors. Evidence regarding the efficacy of interventions is reviewed, and some of the difficulties associated with self-directed programs are discussed. The Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…A series of RCTs showed that this 10-session self-help parenting program could be successfully delivered to parents in rural areas using a self-help workbook alone or in combination with a brief (10-to 30-minute) weekly telephone consultation (Connell et al 1997). The efficacy of this self-help plus telephone-assisted intervention was subsequently replicated and extended and shown to be effective when delivered by regular telephone counseling service for parents (Morawska & Sanders 2006a,b), with parents of disruptive preschoolers (Markie- Dadds & Sanders 2006a,b), and with parents of teenagers (Morawska et al 2005, Stallman & Ralph 2007.…”
Section: Self-help and Telephone-assisted Variantsmentioning
confidence: 94%
“…A series of RCTs showed that this 10-session self-help parenting program could be successfully delivered to parents in rural areas using a self-help workbook alone or in combination with a brief (10-to 30-minute) weekly telephone consultation (Connell et al 1997). The efficacy of this self-help plus telephone-assisted intervention was subsequently replicated and extended and shown to be effective when delivered by regular telephone counseling service for parents (Morawska & Sanders 2006a,b), with parents of disruptive preschoolers (Markie- Dadds & Sanders 2006a,b), and with parents of teenagers (Morawska et al 2005, Stallman & Ralph 2007.…”
Section: Self-help and Telephone-assisted Variantsmentioning
confidence: 94%
“…Coaching has also been used as a strategy for various health professionals to deliver their services: nurses (Huffman, 2007; Lewis & Zahlis, 1997), physicians (Kaplan, 1999), dieticians (Lipscomb, 2006), and occupational therapists (Graham, Rodger, & Ziviani, 2009). Coaching has also been used specifically to support families to: Increase healthy eating and exercise (Gorczynski, Morrow, & Irwin, 2008; Heimendinger et al, 2007; Van Zandvoort, Irwin, & Morrow, 2009);Enhance patient self-management and improve outcomes (Huffman, 2007);Reduce community violence (Kliewer et al, 2006) and domestic violence (Katz & Windecker-Nelson, 2006);Provide family therapy when some family members refuse (McGoldrick & Carter, 2001);Improve parenting skills around health and behavioral challenges (Mabe, Turner, & Josephson, 2001; Morawska, Stallman, Sanders, & Ralph, 2005). Now referred to as health coaching, these strategies differ from traditional health education by emphasizing goal setting, problem solving, and skill building (Butterworth, Linden, & McClay, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Improve parenting skills around health and behavioral challenges (Mabe, Turner, & Josephson, 2001; Morawska, Stallman, Sanders, & Ralph, 2005).…”
Section: Introductionmentioning
confidence: 99%